Open Communicology and citizen science - Sierra-Caballero, Francisco (Anuario ThinkEPI, 2022)
The Digital Age points to the need for an Open Communicology, an applied science of the commons that recognizes the centrality of the subsumption of intellectual work, exploring the decoloniality of knowledge-power from the opening of spaces for cooperation and appropriation of knowledge. These are based on changes in academic production determined by the relevance of the virtual over the face-to-face and the centrality of the social mediation of science, whence the relevance of laying the foundations for a different conception of theoretical practice based on the notion of citizen science. The academic community´s vindication of citizen science presupposes, in this sense, epistemological and cognitive changes, an ethics of the research culture antagonistic to the logic of mercification, and structural political changes in the processes of organization and evaluation of research activity that have to go from the notion of open science to that of complex assemblages based on social experimentation in citizen laboratories.
Keywords: Communicology of the South; Citizen science; Commons; Open science